Acrodermatitis dysmetabolica secondary to isoleucine deficiency in infant with maple syrup urine disease - Fares A. Alkhayal; Sukina Al Haddad; Reem Medhat Bakraa; Abdulmalik Alqahtani (PAGEPress Publications, 2023)
Acrodermatitis dysmetabolica (AD) describes eruptions characterized by the clinical triad of acral dermatitis, diarrhea, and alopecia. AD can be caused by various metabolic disorders one of which is maple syrup urine disease (MSUD). We present a 2-month-old boy diagnosed with MSUD by the age of 5 days and treated with branched-chain amino acid (BCAA) restricted diet, BCAAs formula, and thiamine supplementation. He was referred to dermatology with a 3-week history of diarrhea, progressive acrodermatitis enteropathica like cutaneous eruption and hair loss over the scalp treated with topical mometasone ointment, isoleucine supplementation and leucine restriction. Complete resolution of skin eruption was achieved by 4 weeks, which correlates with normalization of BCAA levels based on close monitoring of biochemical lab values and growth. This case emphasizes the dangers of limiting BCAA intake when treating MSUD, as well as the importance of close monitoring during the amino acid depleting period of growth.